PERSEPSI EMOSIONAL PEMILIK DAN BUKAN PEMILIK TERHADAP HARLEY DAVIDSON - Octawilona Herry, Nadya
Advertising has an important role in running a business. Companies can allocate large funds to advertising to create a perception in the market of the brand. Market perception will greatly influence a brand because perception is one of the main variables that must be considered in creating an advertisement. Apart from luxury brands, it also requires advertising to deliver their products or services to customers. Generally advertisements are classified into emotional or rational based on the messages in the given context. Advertising that involves emotional attraction is the best type of advertising to create a perception of the brand. Emotional appeal can be more easily remembered by people because it can lead directly to the impact of individual behavior. Siliwangi Harley Davidson is the first Harley Davidson luxury brand dealer in Bandung, which was established in 2018. Because Siliwangi Harley Davidson is still brand new, there is no intervention to measure market perceptions of the Harley Davidson brand. So this study is intended to be the first intervention in measuring market perceptions of Harley Davidson luxury brands. But key information is needed, which is emotion that arises from the owners and non-owners of Harley Davidson as informants. This research aims to give new insight to Siliwangi Harley Davidson as a business entity who sells Harley Davidson luxury brands to create future strategies in making emotional advertising. This study uses a qualitative approach to the phenomenological method that uses in-depth interviews in a semistructured way to get emotional perceptions from the informants. Data from in-depth interviews with informants are then processed using textural analysis. The results of textural analysis show that there are positive emotions and negative emotions that arise from the informants on the Harley Davidson brand. Furthermore, the positive emotions that arise from the informants are emotions of kindness, joy, desire, amusement, relaxation, pride, love, satisfaction, and confidence. While the negative emotions that arise are arrogance and annoyance. There is a difference in the appearance of positive emotional perceptions between the owner and non-owner of Harley Davidson, which is emotion of kindness. The findings of this study will be a useful suggestion for Siliwangi Harley Davidson in creating future strategies of making emotional advertisements.